ANALYSIS OF STUDENT’S DIFFICULTIES IN SOLVE CIRCULATION QUESTION IN CLASS VII SMP HARAPAN 2 MEDAN - Narpila, Suci Dahlya; Elfina, Hetty; Wahyuni, Sri; Hasratuddin, Hasratuddin (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2024)
This research began with the researcher's anxiety regarding the low achievement in mathematics learning in class VII SMP Harapan 2 Medan. Considering the importance of mathematics lessons, it is necessary to carry out an analysis regarding the various difficulties students face when finding solutions to mathematical problems. This type of research is qualitative research with research subjects of as many as 14 students in class VII SMP Harapan 2 Medan. From the results of data analysis, it was found that there were four categories of student difficulties when solving mathematics problems on circle material, namely (1) difficulty understanding the concept of circles, radii finger, circumference, and various others; (2) Difficulty using mathematical tools (ruler) in solving mathematical problems; (3) Difficulty in understanding mathematical symbols; and (4) Not being careful in solving mathematics problems